2007
DOI: 10.1111/j.1365-2230.2007.02458.x
|View full text |Cite
|
Sign up to set email alerts
|

The mRNA expression and promoter methylation status of the p16 gene in colony-forming cells with high proliferative potential in patients with psoriasis

Abstract: Our data demonstrate for the first time the abnormal proliferative activity of haematopoietic cells in patients with psoriasis and a profound link between the promoter methylation status and transcriptional activity of p16 and the colony-forming ability of HPP-CFCs, suggesting that haematopoietic cells are involved in psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 28 publications
(48 reference statements)
0
25
0
Order By: Relevance
“…[23], indicating that the hematopoietic microenvironment of the bone marrow in patients with psoriasis was aberrant. In vitro culture of psoriatic bone marrow-derived hematopoietic stem cells indicated that the patient-derived hematopoietic cells had decreased colony formation ability [21,24]. CD4+/CD8+ T cells and CD4+CD25+ regulatory T cells derived from psoriatic bone marrow CD34+ cells in vitro have been found to be functionally similar to those circulating and lesional psoriatic T cells [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…[23], indicating that the hematopoietic microenvironment of the bone marrow in patients with psoriasis was aberrant. In vitro culture of psoriatic bone marrow-derived hematopoietic stem cells indicated that the patient-derived hematopoietic cells had decreased colony formation ability [21,24]. CD4+/CD8+ T cells and CD4+CD25+ regulatory T cells derived from psoriatic bone marrow CD34+ cells in vitro have been found to be functionally similar to those circulating and lesional psoriatic T cells [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…This finding seemed to be biologically plausible, as MTHFR is associated with DNA methylation reactions (Stern et al, 2000) and DNA methylation disorders might play a role in the etiopathogenesis of psoriasis (Ruchusatsawat et al, 2006;Zhang et al, 2007). Moreover, a lower frequency of the tyrosine phosphatase (SHP-1) gene and p16 gene demethylation has been observed in psoriatic skin lesions (Ruchusatsawat et al, 2006;Zhang et al, 2007). However, several case-control studies carried out subsequently have reported inconsistent results (Weger et al, 2008;Vasku et al, 2009;Liew et al, 2012;Asefi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, hypomethylation of p16INK4A (antiapoptotic gene) has been reported in psoriasis, along with demethylation of one of the promoters of the SHP-1 gene, important for keratinocyte growth and proliferation (Ruchusatsawat et al 2006;Zhang et al 2007;Chen et al 2008). Importantly, the findings from these studies provides additional evidence that the molecular defects underlying polygenic skin diseases transcend single-gene mutations, and may be characterized by more global changes at the chromatin level associated with a multitude of downstream effects on gene expression.…”
Section: Aberrant Dna Methylation In Autoimmunerelated Skin Diseasesmentioning
confidence: 56%